Gender Differences in Economics PhD Field Specializations with Correlated Choices - Eva Sierminska; Ronald L. Oaxaca (Institute of Labor Economics (IZA), 2021)
We model the process of field specialization choice among beginning economists within a multivariate logit framework that accommodates single and dual primary field specializations and incorporates correlations among field specialization choices. Conditioning on personal, economic, and institutional variables reveals that women graduate students are less likely to specialize in Labor/Health, Macro/Finance, Industrial Organization, Public Economics, and Development/Growth/International and are more likely to specialize in Agricultural/Resource/Environmental Economics. Field-specific gender faculty ratios and expected relative salaries as well as economics department rankings are significant factors for gender doctoral specialization dissimilarity. Preferences and characteristics contribute about equally to field specialization dissimilarity.
Keywords: J01; J16; J31; 330; gender; economics; specialization; salaries